The characteristics of foam-mat dried red and purple roselle calyces powder prepared with commercial emulsifiers as the foaming agents - Teti Estiasih; Jatmiko Eko Witoyo; Gabriela Kania Mapandin Runtung; Diva Deannova Pasha Moelyono; Alifah Rahmayani Murini; Widiastuti Setyaningsih; Hanifah Nuryani Lioe; Miguel Palma; Kgs Ahmadi (CyTA - Journal of Food)
Roselle flower is an edible flower with health-beneficial bioactive compounds. In this study, red and purple roselle calyces were dried by foam-mat drying with different hydrophilic-lipophilic balance (HLB) of commercial emulsifiers as the foaming agents, including TBM, SP, and SSL. For a comparison is the roselle calyces powder from conventional drying. The mixture of emulsifiers of TBM and SP produces better foam and powder characteristics than a single emulsifier of SSL. HLB value and emulsifier mixture composition affect the foaming properties that influence the powder characteristics. The roselle variety also affected the foaming properties in which purple roselle calyces are better. The antioxidant activity seems to be affected by the foaming stability. The lack of conventional dried roselle calyces powder is the very low solubility indicated by undefined dissolution time. The formation of foam and the use of maltodextrin as a filler contribute to the foam mat-dried powder color.